2011
DOI: 10.4269/ajtmh.2011.11-0159
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Genetic Susceptibility to Developing Early Childhood Diarrhea among Shantytown Children Living in Northeastern Brazil

Abstract: To explore the genetic components of susceptibility to early childhood diarrhea (ECD), we used a quantitative genetic approach to estimate the heritability of ECD among children from two Brazilian favelas. Shared environment was used to model common exposure to environmental factors. Genetic relatedness was determined from pedigree information collected by screening household participants (n = 3,267) from two geographically related favelas located in Fortaleza, Brazil. There were 277 children within these pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Twin studies on infectious diseases have shown higher correlation between monozygotic than dizygotic twins (12)(13)(14). Heritability for early childhood diarrhoea was estimated to be 54% in a pedigreebased design in Brazil (15).…”
Section: Introductionmentioning
confidence: 99%
“…Twin studies on infectious diseases have shown higher correlation between monozygotic than dizygotic twins (12)(13)(14). Heritability for early childhood diarrhoea was estimated to be 54% in a pedigreebased design in Brazil (15).…”
Section: Introductionmentioning
confidence: 99%
“…A reverberating vicious cycle of infection and malnutrition in young children may cause profound long-term deficits in physical and cognitive development, even without overt diarrhea, which can be irreversible [4] . The predisposition and adverse outcomes from repeated or prolonged exposure to C. parvum and other enteric infections may additionally have a strong genetic component in terms of host-parasite and epigenetic interactions [5] , [6] , which could affect the efficacy of nutritional interventions early in life in children at risk in endemic areas [7] and may have long-term consequences. Indeed, we have found that APOE4, the gene associated with increased susceptibility to Alzheimer's disease, is actually protective against early childhood diarrhea and its associated cognitive impairment [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in population genetics often rely on a census-like approach for this. Genealogical data is collected from all households in a population and post-hoc efforts are made to merge the data and remove duplicates (Choh et al 2001;Pinkerton et al 2011). This procedure generally produces one big cluster of related individuals and several minor isolated genealogies, which are usually ignored for the analysis.…”
Section: Participant Selection and Reliabilitymentioning
confidence: 99%